PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TAKE AND GIVE UNTUK MENINGKATKAN HASIL BELAJAR IPA - Ningsih, Seri Winda; Hadiyanti , Putri Octa (Universitas Negeri Medan, 2025)
Abstract: This study aims to improve the learning outcomes of Natural Sciences (IPA) Digestive System material in grade V elementary school students through the application of Take and Give type cooperative learning model. This class action research was conducted in two cycles and used the case study method to describe in depth the changes in student learning outcomes. The research subjects were 32 fifth grade students. Data collection techniques used include learning outcome tests to measure cognitive improvement, observation of student activities during the learning process, and documentation to record important events. Data analysis was carried out by comparing the average value of student learning outcomes in each cycle. The results showed that the average class score and percentage of completeness at the pre-cycle stage, the average class score was 65.5 with a percentage of classical completeness of 40.63%. After the implementation of the Take and Give learning model in Cycle I, the average class score increased to 78.2 with the percentage of classical completeness reaching 71.88%. This improvement continued in Cycle II, where the average class score became 86.9 and the percentage of classical completeness reached 90.63%. The results of the study are expected to make a practical contribution in improving the effectiveness of science learning in elementary schools, especially on the Digestive System material, through the implementation of the Take and Give type cooperative learning model. Keywords: Cooperative learning model, Take and Give type, science, learning outcomes Abstrak: Penelitian ini bertujuan untuk meningkatkan hasil belajar Ilmu Pengetahuan Alam (IPA) materi Sistem Pencernaan pada siswa kelas V Sekolah Dasar melalui penerapan model pembelajaran kooperatif tipe Take and Give. Penelitian tindakan kelas ini dilaksanakan dalam dua siklus dan menggunakan metode studi kasus untuk mendeskripsikan secara mendalam perubahan hasil belajar siswa. Subyek penelitian adalah siswa kelas V sebanyak 32 orang. Teknik pengumpulan data yang digunakan meliputi tes hasil belajar untuk mengukur peningkatan kognitif, observasi aktivitas siswa selama proses pembelajaran, dan dokumentasi untuk mencatat kejadian penting. Analisis data dilakukan dengan membandingkan nilai rata-rata hasil belajar siswa pada setiap siklus. Hasil penelitian menunjukkan bahwa rata-rata nilai kelas dan persentase ketuntasan pada tahap prasiklus, rata-rata nilai kelas adalah 65,5 dengan persentase ketuntasan klasikal sebesar 40,63%. Setelah penerapan model pembelajaran Take and Give pada Siklus I, rata-rata nilai kelas meningkat menjadi 78,2 dengan persentase ketuntasan klasikal mencapai 71,88%. Peningkatan ini terus berlanjut pada Siklus II, di mana rata-rata nilai kelas menjadi 86,9 dan persentase ketuntasan klasikal mencapai 90,63%. Hasil penelitian diharapkan dapat memberikan kontribusi praktis dalam meningkatkan efektivitas pembelajaran IPA di Sekolah Dasar, khususnya pada materi Sistem Pencernaan, melalui implementasi model pembelajaran kooperatif tipe Take and Give. Kata Kunci: Model pembelajaran Kooperatif, Tipe Take and Give, IPA, Hasil Belajar